The Importance of Knowledge, Skill, Attitude and Competence to Achieve Professional Performance: Pentingnya Knowledge,Skill,Attitude dan Kompetensi untuk Mewujudkan Kinerja yang Profesional - Elive Twi Etik; Wisnu Panggah Setiyono (Academia Open, 2021)
This study aims to analyze the effect of knowledge, skills, attitude and competence on professional performance in ASN at the Morokrembangan Kodiklatal Surabaya. The research was conducted using a quantitative approach, with a total sample of 193 ASN in Morokrembangan Kodiklatal Surabaya. The analysis technique used is multiple linear regression analysis, with the help of the SPSS version 25 program. The results show that, 1) knowledge has a significant effect on professional performance, 2) skill has a significant effect on professional performance, 3) attitude has a significant effect on performance. professionals, 4) competence has a significant effect on professional performance, and 5) knowledge, skills, attitudes and competencies on professional performance in ASN at the Morokrembangan Kodiklatal Surabaya.